Efforts to Improve Student Learning Outcomes in Indonesian Language Learning Through Appreciative Principles in Class IV MIS Baiturrahman - Alni; Idami, Rapida; Ainun, Siti Nur (Berpusi Publishing, 2023)
This research aims to improve student learning outcomes in Indonesian language learning. This research is classroom action research. This research was carried out at MIS Baiturrahman Paya Satu Besilam. The research subjects were 32 class IV students consisting of 15 boys and 17 girls. To improve and determine student learning outcomes, this research was carried out through four stages, namely: learning planning, learning implementation, observation, and reflection. Researchers use media and assignment methods to increase student motivation in the form of.